Born-Again Brooklyn: Gates Wires the Library - St Lifer, E (Library journal (1976), 1996)
Describes the Libraries Online program by Microsoft and the American Library Association that provides low-income communities with access to online information by wiring public libraries to the Internet. Highlights activities at the Brooklyn Public Library and discusses earlier pilot projects, including the Technology Resource Institute for Public Libraries in Seattle (Washington). (LRW)